Communication Model Lifestyle of Islamic Adolescents in Religious Life in Semarang City - Saka Mahardika Oktav Nugraha; Juhadi Juhadi; Dewi Liesnoor S; Hamdan Tri Atmaja; Nugroho Trisnu Brata (Universitas Negeri Semarang, 2023)
Communication Model Lifestyle of Islamic adolescents towards religious differences in addressing understanding. Differences between communities on understanding and behavior is a study to carry out a model of communication between Muslim adolescent communities in the city of Semarang. Four Muslim communities have different understandings of behavior and thoughts toward young mosque activist organizations: NU, Muhammadiyah, Tabligh, and LDII. This study examines the communication model of the differences between the four young mosque activist communities in Semarang. Studying the lifestyles of the four religious communities, the extent to which lifestyle differences lead to potential conflicts, and the existence of communication models between the four young mosque activist communities with different understandings. The research method uses a qualitative approach. The research subjects of young mosque activists as the primary informants were based on a purposive sampling technique. The study results are a Communication Model between four religious communities that conflict over differences in understanding. The results of research on the lives of four Muslim communities on lifestyle differences lead to disputes between Muslim communities. Differences in Muslim lifestyles raise potential conflicts between the four Muslim communities of NU, Muhammadiyah, Tabligh, and LDII. The different problems can be integrated with the existence of a social communication model between the four Muslim communities in Semarang.